2018
DOI: 10.1057/s41599-018-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

What has economics got to do with it? The impact of socioeconomic factors on mental health and the case for collective action

Abstract: A clear link exists between social and economic inequality and poor mental health. There is a social gradient in mental health, and higher levels of income inequality are linked to higher prevalence of mental illness. Despite this, in the late 20th and early 21st century, psychiatric and psychological perspectives have dominated mental health research and policy, obscuring root socioeconomic contributors. Drawing on contemporary research on the social determinants of mental health, with particular reference to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 39 publications
2
62
0
1
Order By: Relevance
“…Concern with safe staffing levels in mental health settings is not independent of other critique of ward care and levels of coercion (Baker et al, 2016;Gilburt et al, 2008;Jenkins & Elliott, 2004;Quirk & Lelliott, 2001). The causative factors of mental distress are complex but it is difficult not to take a view that the same economic inequalities squeezing the resources of welfare and health care are also implicated in increasing demand for mental health care (Macintyre, Ferris, Gonçalves, & Quinn, 2018;Stuckler, Reeves, Loopstra, Karanikolos, & McKee, 2018). It is also apparent that mental health services take on an increasingly coercive character when such economic conditions prevail, with, for example, levels of compulsion in England having increased substantially year on year since the banking crisis of 2008 and subsequent austerity (Care Quality Commission, 2017; Thomas, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Concern with safe staffing levels in mental health settings is not independent of other critique of ward care and levels of coercion (Baker et al, 2016;Gilburt et al, 2008;Jenkins & Elliott, 2004;Quirk & Lelliott, 2001). The causative factors of mental distress are complex but it is difficult not to take a view that the same economic inequalities squeezing the resources of welfare and health care are also implicated in increasing demand for mental health care (Macintyre, Ferris, Gonçalves, & Quinn, 2018;Stuckler, Reeves, Loopstra, Karanikolos, & McKee, 2018). It is also apparent that mental health services take on an increasingly coercive character when such economic conditions prevail, with, for example, levels of compulsion in England having increased substantially year on year since the banking crisis of 2008 and subsequent austerity (Care Quality Commission, 2017; Thomas, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The mental health of individuals is shaped by the social, environmental and economic conditions in which they are born, grow, work and age. [4][5][6][7] Poverty and deprivation are key determinants of children's social and behavioural development 8,9 and adult mental health. 10 In Scotland, individuals living in the most deprived areas report higher levels of mental ill health and lower levels of well-being than those living in the most affluent areas.…”
Section: Poverty and Mental Healthmentioning
confidence: 99%
“…The assumption being that such progress has been made that these issues are now resolved. Macintyre et al (2018) [ 3 ] emphasised the importance of a consideration of the links between social economic factors and the occurrence and experience of mental health problems. There have been significant moves toward this but the continued dominance of medical and individualised approaches to mental distress prevents a full consideration of the impact of socio-economic factors (Shim et al 2014) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been significant moves toward this but the continued dominance of medical and individualised approaches to mental distress prevents a full consideration of the impact of socio-economic factors (Shim et al 2014) [ 4 ]. Macintyre et al (2018) [ 3 ] concluded that such an analysis that starts from a socioeconomic position can be the basis for a move towards a social justice approach for mental health. This paper explores these debates within the context of the impact of the social and economic policies of austerity that have been pursued in the UK since 2010.…”
Section: Introductionmentioning
confidence: 99%